Comparison of eleven RNA extraction methods for poliovirus direct molecular detection in stool samples - Akello,J; Bujaki,E; Shaw,A; Khurshid,A; Arshad,Y; Troman,C; Majumdar,M; O'Toole,Á; Rambaut,A; Alam,MM; Martin,J; Grassly,N (Microbiology Spectrum, 2023)
Direct detection by PCR of poliovirus RNA in stool samples provides a rapid diagnostic and surveillance tool that can replace virus isolation by cell culture in global polio surveillance. The sensitivity of direct detection methods is likely to depend on the choice of RNA extraction method and sample volume. We report a comparative analysis of 11 nucleic acid extraction methods (7 manual and 4 semiautomated) for poliovirus molecular detection using stool samples (n = 59) that had been previously identified as poliovirus positive by cell culture. To assess the effect of RNA recovery methods, extracted RNA using each of the 11 methods was tested with a poliovirus-specific reverse transcription-quantitative PCR (RT-qPCR), a pan-poliovirus RT-PCR (near-whole-genome amplification), a pan-enterovirus RT-PCR (entire capsid region), and a nested VP1 PCR that is the basis of a direct detection method based on nanopore sequencing. We also assessed extracted RNA integrity and quantity. The overall effect of extraction method on poliovirus PCR amplification assays tested in this study was found to be statistically significant (P < 0.001), thus indicating that the choice of RNA extraction method is an important component that needs to be carefully considered for any diagnostic based on nucleic acid amplification. Performance of the methods was generally consistent across the different assays used. Of the 11 extraction methods tested, the MagMAX viral RNA isolation kit used manually or automatically was found to be the preferable method for poliovirus molecular direct detection considering performance, cost, and processing time.